Clinical-epidemiological study on Fournier's gangrene in a Luanda hospital. From January 2016 to December 2021 - Tomas Ariel Lombardo Vaillant (Medisur)
Background: Fournier's gangrene is a serious polymicrobial infection caused by microorganisms that act synergistically and determine a progressive necrotizing fasciitis in the scrotum and perineum with manifestations of sepsis that can progress to septic shock and organ failure. Objective: to characterize clinically and epidemiologically Fournier's gangrene in patients diagnosed in a reference hospital unit. Methods: retrospective, observational and descriptive study based on the analysis of the clinical records of 64 male patients with Fournier's gangrene, diagnosed at the Hospital Militar Principal/Instituto Superior de Luanda, Republic of Angola from January 2016 to December 2020. Study variables were: age, toxic habits, comorbidity, clinical manifestations, extension, location as well as its evolution. The quantitative variables were expressed as means, median and range, while the qualitative variables were expressed in terms of absolute numbers and percentages. Results: the average age was 45.09 years; 36 patients (56.2%) consume alcoholic drink and 14 (21.87%) declared smoking habits. The main comorbidity was diabetes mellitus in 21 (32.8%). Pain with increased scrotal volume predominated in 43 (67.2%) subjects; early surgical debridement with antibiotic therapy was the key to management. Five patients died. Conclusions: Fourner's gangrene is a serious disease that can present systemic repercussions and death. The cornerstone of treatment is early surgical debridement supported by support measures. The series presented showed adequate and effective multidisciplinary management.